2008
DOI: 10.1021/jp076779h
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Photochemical C−N Bond Cleavage in CH3N3:  A New Photochemical Route to Cyclic N3

Abstract: We report VUV-photoionization based photofragmentation-translational spectroscopy data, providing a comprehensive study of the collision free photochemistry of methyl azide (CH3N3) at 193 nm. We report the first observation of the production of methyl and the N3 radical and derive the translational energy release distribution of this reaction. The most probable translation energy is only 8%, and the maximum translational energy is only 60% of the available energy, taking CH3 + linear N3 as the zero of energy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…Although mechanistically complex, the various photochemical channels of methyl azide are easily disentangled with PTS, as has been previously demonstrated. 18,20,21 Our ability to discriminate by time-of-flight (TOF), detected massto-charge ratio, and the synchrotron photon energy, hν synch , allows us to selectively look at all the products, essentially one by one. This greatly simplifies the assignment of the ion signal to its neutral photofragment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although mechanistically complex, the various photochemical channels of methyl azide are easily disentangled with PTS, as has been previously demonstrated. 18,20,21 Our ability to discriminate by time-of-flight (TOF), detected massto-charge ratio, and the synchrotron photon energy, hν synch , allows us to selectively look at all the products, essentially one by one. This greatly simplifies the assignment of the ion signal to its neutral photofragment.…”
Section: Resultsmentioning
confidence: 99%
“…Rydberg H-atom time-of-flight studies of hydrazoic acid (HN 3 ) photolysis suggest cyclic-N 3 formation, 16,17 and clear evidence is found in the near threshold VUV photoionization-based PTS measurements on methyl azide (CH 3 N 3 ) photodissociation at 193 nm. 18 A complete review is available. 19 Due to both its energetics and dynamics, methyl azide is a potentially interesting precursor for cyclic-N 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the existence of neutral HEF-N 3 was confirmed in experiments [53] with photolysis of HN 3 containing labeled hydrogen atoms. A very recent experimental study [54] reported on detection of relatively long-living cyclic N 3 species (microsecond lifetime) produced by photochemical decomposition of methyl azide, CH 3 N 3 , irradiated at a wavelength of 196 nm.…”
Section: Synthesis Of Nmentioning
confidence: 99%
“…A great deal of research has been carried out to assign the microwave, infrared, and electronic spectrum of this moiety [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. As a reactive species, MI can dissociate by 1,2-elimination of H 2 which has been studied both experimentally and theoretically [44][45][46][47][48][49][50][51][52][53][54][55]. Vinylamine and ethyleneimine are chemicals that widely used in industry; they were first detected as primary pyrolysis product of EA in the gas phase using microwave spectroscopic technique by Lovas et al [1,2].…”
Section: Introductionmentioning
confidence: 99%